Peranan Ayah Dalam Mendidik Anak Menurut Al-Qur’an - M. Yemmardotillah, Eka Eramahi, Ilham (Continuous Education: Journal of Science and Research, 2021)
In the family the father is a figure who plays a role in the growth, development and success of the child. Fathers are responsible for giving advice to their children. This research discusses the role of fathers in educating children according to the Qur'an. This study examines the verses of the al-Qur'an which are related to the role of the father in educating children according to the al-Qur'an. This research uses library research or also called library research. This study uses a descriptive analysis method with a classical-contemporary interpretation paradigm approach. The data collection was carried out thematically, namely collecting the verses of the Qur'an in various letters that have a relationship about the role of the father. The results showed that in the Qur'an it is explained that there are several verses that describe the role of fathers in educating their children, so that this method is relevant to be realized in the contemporary context. The father figure in question is Prophet Nuh, Prophet Ibrahim, Prophet Ya'qub, and Luqman. Among the roles are as educators and caregivers for their children, as role modes for children, creating togetherness with children, and as protectors in the family.